Implementasi Model Kolaborasi Partisipatif dalam Pengabdian Masyarakat: (Studi Kasus Integrasi Program Edukasi dan Religius untuk Peningkatan Kapasitas SDM di Desa Sugihen) - Maulana Firjatullah; Siti Aisyah; Syabina Adinda Putri; Khairul Fajar; Ismail Abu Rizal Padang (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
This study investigates a participatory collaboration model in community service at Sugihen Village by integrating educational and religious programs. Using a qualitative case study approach during a community service program (July–September 2025), data were collected through observation, interviews, and documentation. The findings reveal that educational programs, such as financial literacy, anti-bullying seminars, and tutoring, alongside religious activities like Qur’an recitation and Islamic festivals, significantly improved practical skills, moral values, and social cohesion among community members. Active community participation was found to foster shared ownership, creating a sense of responsibility and ensuring sustainability. The collaborative approach not only empowered individuals but also strengthened the social fabric of the village, promoting community engagement in both educational and religious activities. The model demonstrates its effectiveness in enhancing human resource capacity holistically. Moreover, it is replicable in other rural contexts, offering a sustainable framework for community development through the integration of education and religious practices.